Placental Mitochondrial Toxicity, Oxidative Stress, Apoptosis, and Adverse Perinatal Outcomes in HIV Pregnancies Under Antiretroviral Treatment Containing Zidovudine. (1st August 2017) - Hernández, Sandra; Catalán-García, Marc; Morén, Constanza; García-Otero, Laura; López, Marta; Guitart-Mampel, Mariona; Milisenda, José; Coll, Oriol; Cardellach, Francesc; Gratacós, Eduard; Miró, Òscar; Garrabou, Glòria
Abstract : Objective: To determine whether mitochondrial, oxidative, and apoptotic abnormalities in placenta derived from HIV and combined antiretroviral therapy (cART) containing zidovudine (AZT) could be associated with adverse perinatal outcome. Design: Cross-sectional, controlled, observational study. Methods: We studied obstetric results and mitochondrial, oxidative, and apoptotic state in placenta of 24 treated HIV-infected and 32 -uninfected pregnant women. We measured mitochondrial DNA (mtDNA) content by quantitative reverse transcriptase–polymerase chain reaction (mtND2/n18SrRNA), oxidative stress by the spectrophotometric quantification of lipid peroxidation and apoptosis by Western blot analysis of active caspase-3 respect to β-actin content and analysis of the terminal deoxynucleotidyl transferase dUTP nick end labeling. Results: Global adverse perinatal outcome (defined as preterm delivery or/and small newborns for gestational age) was significantly increased in HIV pregnancies [or 6.7 (1.3–33.2); P < 0.05]. mtDNA content in HIV-infected women was significantly depleted (39.20% ± 2.78%) with respect to controls (0.59 ± 0.03 vs. 0.97 ± 0.07; P < 0.001). A significant 29.50% ± 9.14% increase in oxidative stress was found in placentas of HIV-infected women (23.23 ± 1.64 vs. 17.94 ± 1.03; P < 0.01). A trend toward 41.18% ± 29.41% increased apoptosis active caspase-3/β-actin was found in HIV patients (0.48 ± 0.10 vs. 0.34 ± 0.05; P = not significant), confirmed by transferase dUTP nick end labeling assay. Adverse perinatal outcome did not correlate mitochondrial, oxidative, or apoptotic findings. Conclusions: Placentas of HIV-infected pregnant women under AZT cART showed evidence of mtDNA depletion, increased oxidative stress levels, and apoptosis suggestive of secondary mitochondrial failure, potential base of associated adverse perinatal outcome. Despite the fact that further demonstration of causality would need new approaches and bigger sample sizes, AZT-sparing cART should be considered in the context of pregnancy.